The The Influence Of Brand Image And Product Innovation On Starbucks Coffee Purchase Decisions In Surabaya City - Dharmani, I.G.A. Aju Nitya; Baktiono, Agus; Ashari, Chriestine Ayu (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: Along with the urban lifestyle, the development and growth of culinary businesses are currently increasing in Indonesia, especially in the city of Surabaya, this is marked by the rise of restaurants, cafes and coffee shops. Starbucks Coffee Indonesia now has 22 coffee outlets in the city of Surabaya. Starbucks strives to present an extraordinary legacy and experience in every cup. This study aims to analyze the influence of brand image and product innovation on coffee purchasing decisions at Starbucks coffee shops in the city of Surabaya. This research is a quantitative study. Deign/Methodology/Approach: The number of samples in this study was 104 Starbucks Coffee consumers taken from 22 Starbucks coffee outlets in the city of Surabaya using accidental sampling techniques. Researchers used interviews, questionnaires and observations to obtain data. Findings: The results of the study showed that partially brand image and product innovation had a significant effect on consumer purchasing decisions for Starbucks coffee in the city of Surabaya. Furthermore, Brand Image and Product Innovation simultaneously had a significant effect on Starbucks Coffee purchasing decisions at coffee outlets in the city of Surabaya. This shows that in the midst of the highly competitive business competition between foreign and local coffee shops in Surabaya, Starbucks coffee can still survive and carry out its business activities sustainably through the brand image it carries and innovating the products it offers. Paper Type: Research Paper